Internalization of Islamic Values in the Toilet Training Learning Process at RA SBB Cahaya Ilahi, Serang City: A Case Study - Safitri, Fifit; Effendi, Moh Mahfud; Ekowati, Dyah Worowirastri (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – Toilet training in early childhood education is commonly treated as a matter of independence, bodily control, and hygiene. In Islamic early childhood settings, however, it may also function as a routine through which aqidah, sharia, akhlaq, and thaharah are introduced and practiced. What remains less clear is how this ordinary bodily routine becomes a medium of value internalization in everyday school life. This article examines how Islamic values were internalized through toilet training activities at RA SBB Cahaya Ilahi, Serang City, and how that process became visible in children’s behavior.Design/methods/approach – A qualitative descriptive case study was conducted with Group B students, the principal, classroom teachers, and assistant teachers. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. Credibility was strengthened through source and technique triangulation.Findings – Islamic values were internalized through a four-stage process of introduction, habituation, reinforcement, and evaluation embedded in the school’s daily toileting routine. Toilet training therefore operated not only as a hygiene practice but also as an embodied pedagogical routine in which prayer, etiquette, modesty, responsibility, and cleanliness were repeatedly taught and monitored. The outcomes of this process were visible in children’s behavior across aqidah, sharia, akhlaq, and thaharah domains. At the same time, internalization was uneven. Brief and highly repeated actions such as prayer recitation and entry and exit etiquette appeared more stable than actions requiring fuller bodily coordination and more complete procedural follow-through.Research implications/limitations – The findings suggest that value internalization in early childhood is structured, mediated, and uneven rather than automatic. At the same time, the study is limited to one Islamic early childhood institution and does not fully capture the continuity between school-based habituation and family practice.Practical implications – Islamic early childhood institutions can use daily care routines such as toilet training as structured sites of character education by linking bodily procedures with value language, consistent teacher guidance, reinforcement, and family continuity.Originality/value – The article brings toilet training research into conversation with Islamic value education and shows that toilet training can be understood not merely as a developmental routine, but as an embodied pedagogical mechanism through which religious values are translated into children’s daily conduct.Paper type Case study